Analisa Pandemi Covid-19 terhadap Gangguan Psikosomatis pada Masyarakat yang Bertempat Tinggal Berdekatan dengan Fasilitas Kesehatan - Eky Okviana Armyati; Sri Susanti; Siti Munawaroh (Syntax Corporation Indonesia, 2021)
This Covid-19 pandemic problem began to enter our country around 2020. At that time, all Indonesian people were in confusion The Indonesian people and even the state don't really understand what Covid-19 is because the case was originally in Wuahn China. But over time the virus will also spread everywhere, even in Indonesia. With the entry of the virus in Indonesia, all aspects of Indonesia began to die and weaken, for example, the economy, tourism, food sector, etc., all began to have problems. In addition to fields related to humans, it is also very influential on humans themselves, such as feeling afraid, feeling uncomfortable and also feeling stressed and some are even depressed about this covid case. This happens because of the many deadly cases of this covid. With this, researchers are interested in knowing how the psychological condition of the people who live around health services. This psychosomatic disorder affects the mental health of the community as well as the physical health of the community, especially those who live around the health service area. This research method uses descriptive analysis. Where with this analysis we will find out what are the impacts of the COVID-19 pandemic. Based on the results of the study, it was found that the mean value was 1.2667 and the median value was 1.00 with a standard deviation of 4.4978 with a 2.00 percentile for psychosomatic disorders, this indicates that there is indeed an influence between psychosomatics and covid -19. Based on the results of the study, it was found that the mean value was 1.2667 and the median value was 1.00 with a standard deviation of 4.4978 with a 2.00 percentile for psychosomatic disorders, this indicates that there is indeed an influence between psychosomatics and covid -19. Thus it can be concluded that every time the community hears the word covid and also the increasing number of covid this will cause many people to experience psychosomatic disorders such as experiencing anxiety and also leading to depression.